Challenges and opportunities of India's enhanced participation in the global economy - Joumard, Isabelle (OECD Economics Department Working Papers, 2020)
India is becoming a key player in the global economy. It performs well in exporting information and technology services, pharmaceuticals and petroleum products. India's large diaspora is well integrated abroad, helping to develop new export markets and facilitate the transfer of technology and know-how. India could perform better in some domains. These include labour-intensive manufacturing exports and foreign direct investment. Better performance in these areas would boost job creation and thus make growth more inclusive. It would require improving further infrastructure, in particular transport and energy provision, modernising product market regulations, developing skills, and reconsidering barriers to trade and investment. OECD simulations suggest that India would be a major beneficiary were barriers to trade and investment be reduced multilaterally. In the absence of a multilateral agreement, the economy would also gain from a unilateral liberalisation of trade and investment. This Working Paper relates to the 2019 OECD Economic Survey of India http://www.oecd.org/economy/india-economic-snapshot